PENGALAMAN KOMUNIKASI MAHASISWA UPN VETERAN JAKARTA DALAM PEMBELAJARAN ONLINE - Eva Oktaviani (2021)
Starting from the implementation of online learning at UPN Veterans Jakarta since March 16, 2020, which was caused by the COVID-19 virus pandemic, it became an interesting phenomenon, because this was the first time it was implemented at UPN Veterans Jakarta. The transition from face-to-face learning or offline learning to a distance learning system or online provides a new experience for the world of education, especially changes in communication. In this study, it is intended to determine the phenomenon of the implementation of online learning which is currently ongoing for more than one year. Thus, this study focuses on digging deeper into the communication experiences of ten UPN Veteran Jakarta students in carrying out online learning. By using the phenomenological method, this study explains the concept of meaning and experience of subjects who have special characteristics. Meanwhile, related to the method used by the researcher, the questions from this research are: 1) What are the views of UPN Veteran Jakarta students regarding online learning?, 2) How is the communication experience of UPN Veteran Jakarta students in online learning? 3) What themes are considered important in online learning? 4) What is the essence of online learning conducted by UPN Veteran Jakarta students. Through in-depth interviews made by ten UPN Veterans Jakarta students with an average duration of 30 to 180 minutes which shows the results of the study that the themes obtained from UPN Veterans Jakarta students, namely: interaction becomes limited, Stress, Difficulty getting feedback, Limiting creative freedom, Internet signal, Lots of noise, Novelty, more flexible time and freedom of dress.